Direct Anterior Insular Cortex Stimulation Increases Heat Pain Threshold: A Case Report. (1st September 2019) - Liu, Chang-Chia; Moosa, Shayan; Quigg, Mark; Elias, W Jeffrey
Abstract: INTRODUCTION: The insular cortex is thought to be involved in the cerebral processing of three dissociable dimensions of pain: sensory-discriminative, affective-motivational, and cognitive-evaluative. The posterior portion of the insular cortex (pIC) has greater connectivity to the primary and secondary somatosensory cortices and is likely related to the sensory-discriminative dimension of pain. The anterior portion the of insular cortex (aIC) has greater connectivity to the ventrolateral prefrontal and orbitofrontal cortices and is involved in the affective-motivational and cognitive-evaluative aspects of pain. While direct pIC stimulation has been demonstrated to increase thermal pain threshold, direct aIC stimulation has never been attempted in humans. We hypothesize that direct aIC stimulation will induce an inhibitory effect upon cerebral processing of the affective components of pain and therefore will result in a significant increase in thermal pain threshold. METHODS: A 31-yr-old female patient undergoing epileptic focus localization with depth electrodes implanted in the aIC was recruited for this study. The locations of the aIC electrodes were determined by postoperative T2-weighted MRI. Direct aIC stimulation was performed with the following settings: bipolar mode, 3 trains of 10 s stimulations at a frequency of 50 Hz, pulse width of 250 μs, and interstimulus train intervals of 5 s. The intensity of stimulation was set to 2 mA and 4 mA. Thermal pain thresholds were measured on the contralateral forearm following direct aIC stimulation. RESULTS: Direct aIC stimulation increased the heat pain threshold by 2°C, and the magnitude of this effect was positively correlated with the intensity of stimulation ( P = .011). No evoked sensations were reported. CONCLUSION: This case suggests that direct aIC stimulation decreases thermal nociception and provides evidence that the aIC may be a neuromodulation target for chronic pain treatment.